Evaluating AI Responses: A Step-by-Step Approach for Test Automation - Ramachandran, Sooraj (Eastasouth Institute, 2025)
Artificial Intelligence (AI) applications are transforming business operations, yet ensuring the accuracy, relevance, and reliability of AI-generated responses remains a critical challenge. This paper explores various methodologies for AI response evaluation, progressing from basic string comparisons to machine learning (ML)-based assessments and advanced Retrieval-Augmented Generation (RAG) techniques. We examine the advantages and limitations of each approach, illustrating their applicability with C# implementations. Our findings suggest that while traditional methods like fuzzy matching provide quick validation, ML-based and RAG-based approaches offer superior contextual understanding and accuracy. The study highlights the importance of automated evaluation pipelines for AI systems and discusses future research directions in improving AI response testing methodologies.